EFFECT OF MANCOZEB 80% CONCENTRATIONS ON THE GROWTH OF CENOCOCCUM GEOPHILUM FR. UNDER IN VITRO CONDITION - SUPRIYANTO SUPRIYANTO (SEAMEO BIOTROP, 2005)
Fungicides, such as Mancozeb 80% are used in nurseries to prevent the plant root against pathogenic fungi. These fungicides may have negative impacts on beneficial organisms such as ectomycorrhizal fungi. Cenococcum geophilum is an important ectomycorrhizal fungus associated with some forest trees species. An in vitro experiment was conducted in laboratory condition. Cenococcum geophilum was cultured on solid Modified Melin Nokrans’ (MMN) medium containing Mancozeb 80 % at different concentrations (0, 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, and 1000 μM). A completely randomized design was used with 8 replicates Petri dishes. Mancozeb 80 % decreased the growth of mycelia of C. geophilum. The radial growth of mycelia was not inhibited by Mancozeb 80 % at 0 to 400 μM concentrations. Fungi-static effect of Mancozeb 80 % was found at 500 to 600 μM concentrations, meanwhile fungi-toxic effect of Mancozeb 80 % was obtained at concentration more than 700 μM. A lethal level of Mancozeb 80% to the growth of C. geophilum was not found. Key word : fungicide/Mancozeb 80 % /Cenococcum geophilum/fungi-static, fungi-toxic